PERBANDINGAN HASIL BELAJAR SISWA PADA MATERI POKOK SISTEM PERSAMAAN LINEAR DUA VARIABEL DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DAN MODEL PEMBELAJARAN LANGSUNG DI KELAS X SMA NEGERI 8 PADANGSIDIMPUAN - Jumaita Nopriani Lubis (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2019)
Abstract: The aim of the research was to know the describing students’ achievement in two variables linear equation system by using Cooperative Learning Model STAD and Direct Study Model at the tenth grade students of SMA Negeri 8 Padangsidimpuan. The writer wanted to know whether the differences students’ achievement in teaching two variables linear equation system. The population of this research was all the tenth grade students of SMA Negeri 8 Padangsidimpuan which include 138 students or 5 classes. By using cluster sampling technique,the writer took 56 students. The data was analyzed by using two ways,descriptive analysis and ttest formulation. Test was used to collect the data. Based on the data analysis,it could be found that students’ achievement in teaching two variables linear equation system by using STAD was 77.5. While students’ achievement in teaching two variables linear equation system by using Direct Learning model was 69.82. The both models were categorized “good”. Based on the calculation, it could be found that t count = 2.82, error level 5%, df = n1 + n2 – 2 = 28 + 28 – 2 = 54. While t table = 1.673. Based on the calculation above, it could be seen that t count > t table (2.82>1.673). It means the hypothesis was accepted. In the other words, there was a significant difference between Cooperative Learning Model STAD and Direct Study model in teaching two variables linear equation system at the tenth grade students of SMA Negeri 8 Padangsidimpuan. Key words : Two variables linear equation system, Cooperative Learning Model STAD, Direct Study Model